A generalized model of human body radiative heat exchanges for optimal design of indoor thermal comfort conditions - Marino, Concettina; Nucara, Antonino; Peri, Giorgia; Pietrafesa, Matilde; Rizzo, Gianfranco (Solar energy, 2018)
•A tool assessing the radiative heat exchanges in confined spaces is presented.•The procedure complexity is scalable on the level of accuracy needed.•The spatial and time changes of the radiant field are considered.•The influence of the solar radiation on human body thermal balance is considered.•The tool is intended for designers/researchers for thermal comfort evaluation. Human thermal sensation depends heavily on radiative exchanges between the human body and the surrounding environment. Because these exchanges play a crucial role in the thermal balance of the human body, about 35% of the process, human thermal sensation should draw the attention of planners when designing both indoor environments and equipment. The present study aims to contribute to this field by proposing a procedure for delineating the optimal comfort conditions for occupants in most of the articulate and realistic configurations of actual indoor environments. Specifically, this procedure enables accurate assessment of the radiant field surrounding a subject in a given indoor realistic environment and considers its variability with space and time along with the presence of high-intensity radiant sources. The proposed simulation tool contains a set of algorithms in which the degree of complexity depends on the level of accuracy for modelling the radiative heat transfer between the occupants and surrounding environment. The feasibility of these algorithms for designers and researchers has also been checked for a single room characterised by the presence of windows in two different exposures. This configuration implies a complex pattern of the sun entering the room, which in turn determines relevant spatial modifications of the indoor comfort thermal conditions. Such complex situations are effectively interpreted by the proposed model. This analysis provides useful indications for suitable design of layouts of the confined space and the size of an effective heating, ventilating, and air conditioning system to limit the discomfort felt inside the room.